Vis-NIR soil spectral library of the Hungarian Soil Degradation Observation System - János Mészáros; Zsófia Kovács; Péter László; Szilvia Vass-Meyndt; Sándor Koós; Béla Pirkó; Nóra Szűcs-Vásárhelyi; Zsófia Bakacsi; Annamária Laborczi; Kitti Balog; László Pásztor (Scientific Data)
Abstract Since soil spectroscopy is considered to be a fast, simple, accurate and non-destructive analytical method, its application can be integrated with wet analysis as an alternative. Therefore, development of national-level soil spectral libraries containing information about all soil types represented in a country is continuously increasing to serve as a basis for calibrated predictive models capable of assessing physical and chemical parameters of soils at multiple spatial scales. In this article, we present a database containing laboratory and visible-near infrared spectral data of legacy soil samples from the Hungarian Soil Degradation Observation System (HSDOS). The published data set includes the following parameters measured in 5,490 soil samples: pHKCl, soil organic matter (SOM), calcium carbonate (CaCO3), total salt content (TSC), total nitrogen (TN), soluble phosphorus (P2O5-AL), soluble potassium (K2O-AL), plasticity index according to Hungarian standard (PLI), soil profile depth and reflectance data between 350 and 2,500 nm wavelength. The presented database can be a complement for further soil related research on continental, national or regional scales to support sustainable soil management.